2016
DOI: 10.1155/2016/5137386
|View full text |Cite
|
Sign up to set email alerts
|

Polysaccharide Extracted from Laminaria japonica Delays Intrinsic Skin Aging in Mice

Abstract: This study aimed to determine the effect of topically applied Laminaria polysaccharide (LP) on skin aging. We applied ointment containing LP (10, 25, and 50 μg/g) or vitamin E (10 μg/g) to the dorsal skin of aging mice for 12 months and young control mice for 4 weeks. Electron microscopy analysis of skin samples revealed that LP increased dermal thickness and skin collagen content. Tissue inhibitor of metalloprotease- (TIMP-) 1 expression was upregulated while that of matrix metalloproteinase- (MMP-) 1 was dow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 43 publications
0
6
0
1
Order By: Relevance
“…In this study, we found that LJE can augment the expression of nc886 to defend the cells exposed to UVB damage. LJE functions as an extra layer of protection against UVB and nc886 regulated the expression of IL-8 and TNF-α increased by UVB exposure ( Figure 1 ) [ 5 , 6 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we found that LJE can augment the expression of nc886 to defend the cells exposed to UVB damage. LJE functions as an extra layer of protection against UVB and nc886 regulated the expression of IL-8 and TNF-α increased by UVB exposure ( Figure 1 ) [ 5 , 6 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Its versatility is likely from its water-soluble fibers (i.e., alginate and fucoidan) and other fat-soluble ingredients (e.g., fucosterol, fucoxanthin, magnesium, calcium, iron, zinc). Additionally, kelp possesses plenty of polysaccharides that provide anti-inflammatory and antioxidant effects [ 5 , 6 ]. Studies have attempted to use these anti-inflammatory and antioxidant properties to protect skin from the increasing environmental hazards.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It comprises various layers, including the epidermis and dermis. These layers form a protective barrier from environmental stresses, such as heat, infection, oxidative activity, and water loss [ 1 , 2 , 3 ]. Skin aging occurs due to two biochemical processes.…”
Section: Introductionmentioning
confidence: 99%
“…As the largest protective barrier of the human body, the skin is sensitive to aging, and collagen and skin elasticity decline when aging occurs [3, 39]. Experimentally, Hyp is a major component of collagen that plays a key role in collagen stability [40].…”
Section: Discussionmentioning
confidence: 99%